Lung transplantation for pulmonary chronic graft-versus-host disease: a missed opportunity? - Andrea Zajacova, MD; Hélène Schoemans, MD, PhD; Mark Greer, MD, MRCP; Hildegard Greinix, MD; Peter Jaksch, MD; Osnat Shtraichman, MD; Rayid Abdulqawi, MD, PhD; Are M. Holm, MD, PhD; Robin Vos, MD, PhD; Saskia Bos, MD, PhD (JHLT Open)
Chronic graft-versus-host disease is a common complication after allogeneic hematopoietic stem cell transplantation, with pulmonary chronic graft-versus-host disease (PcGvHD) particularly associated with a dismal prognosis. Lung transplantation (LuTx) is a final therapeutic option for well-selected patients affected by this condition. Nevertheless, only a small group of PcGvHD patients are referred for LuTx. This review addresses common concerns regarding referral and listing of PcGvHD patients for LuTx (such as risk of relapse of hematological malignancy, infectious complications and rejection) and survival outcomes of this specific cohort of patients. Importantly, LuTx for PcGvHD has comparable outcomes to other indications. The establishment of specific LuTx indication criteria for PcGvHD patients may improve referral rates and timing of both referral and listing of suitable candidates.